PATRIARCHAL CULTURE IN THE MOVIE THE PREY (2022) - Adiyani, Lady Khairunnisa; Kayana, Kemala Azmi; Wijaya, Sofia Emanuella; Adha, Tharissya Pra; Pratama, Ristyawan; Karnanta, Kukuh Yudha (Jurusan Sastra Indonesia, 2023)
This research aims to analyze the portrayal of a female character in fighting patriarchal culture in the film The Prey (2022). This research uses the theory of patriarchy by Allan G. Johnson and qualitative method by John Fiske's semiotics. This uses The Codes of Television, which are divided into three levels: reality, representation, and ideology. The results of this study show that in the movie The Prey (2022), patriarchal culture has become the root of life in the Comanche tribe. Therefore, a movement against patriarchy is required, as demonstrated by the character Naru in the film The Prey (2022).